Poziom wydolnosci i jego ocena u uczennic oraz uczniów szkoly o profilu sportowym w Warszawie - Timoszenkow, W.; Starosta, W.; Timoszenkowa, A.; Pawlowa-Starosta, T. (Sport wyczynowy, 2002)
The goal of our research was to measure and evaluate the level of endurance on a 5-point scale. The research material consisted of 158 subjects, aged 10 to 14, including 86 boys and 72 girls. All of them were pupils in a Warsaw school with a sports emphasis. The primary research instruments were the Timoshenkov test, consisting of 20 knee bends performed within 20 seconds, and repeated measurements of the pulse rate based on the short functional trial of Martinet and Martinet-Kuszelewski. The data we gathered indicate that the training load for 10-11-year olds enrolled in a general physical development preparatory program is excessive, as is the load applied to 12-14-year olds specializing in track and field or fencing. A lower load was established for girls in comparison to boys of the same age. The continuation of such non-optimal loads with reference to our subjects could cause adverse changes in the organism of the trainees (over-training ) and a considerable deterioration of their sports results. The results of the present study point to the necessity for periodic monitoring of the training loads applied and their impact on the organism of the trainees, using methods that are simple and at the same time objective. Among such methods is the Timoshenkov test.